Prediction of long‐term prognosis by heteroplasmy levels of the m.3243A>G mutation in patients with the mitochondrial encephalomyopathy, lactic acidosis and stroke‐like episodes syndrome. (21st November 2016) - Fayssoil, A.; Laforêt, P.; Bougouin, W.; Jardel, C.; Lombès, A.; Bécane, H. M.; Berber, N.; Stojkovic, T.; Béhin, A.; Eymard, B.; Duboc, D.; Wahbi, K.
Abstract : Background and purpose: Our aim was to determine the prognostic value of urine and blood heteroplasmy in patients with the m.3243A>G mutation. Methods: Adults with the m.3243A>G mutation referred to our institution between January 2000 and May 2014 were retrospectively included. The relationship between their baseline clinical characteristics, their mutation load in urine and blood, and major adverse events (MAEs) during follow‐up, defined as medical complications requiring a hospitalization or complicated by death, was studied. Results: Of the 43 patients (age 45.6 ± 13.3 years) included in the study, 36 patients were symptomatic, including nine with evidence of focal brain involvement, and seven were asymptomatic. Over a 5.5 ± 4.0 year mean follow‐up duration, 14 patients (33%) developed MAEs. Patients with MAEs had a higher mutation load than others in urine (60.1% ± 13.8% vs. 40.6% ± 26.2%, P = 0.01) and in blood (26.9% ± 18.4% vs. 16.0% ± 12.1%, P = 0.03). Optimal cutoff values for the prediction of MAEs were 45% for urine and 35% for blood. In multivariate analysis, mutation load in urine ≥45% [odds ratio 25.3; 95% confidence interval (CI) 1.1–567.8; P = 0.04], left ventricular hypertrophy (odds ratio 16.7; 95% CI 1.3– 222.5; P = 0.03) and seizures (odds ratio 48.3; 95% CI 2.5–933; P = 0.01) were associated with MAEs. Conclusions: Patients with the m.3243A>G mutation are at high risk of MAEs, which can be independently predicted by mutation load in urine ≥45%, a personal history of seizures, and left ventricular hypertrophy. Abstract : Clickhere to view the accompanying paper in this issue.